Lived experiences of nursing students regarding learning in large classes and its effects on teaching and learning at the University of Namibia - Trymore B. Nhokwara; Daniel O. Ashipala; Medusalem H. Joel (AOSIS, 2022)
Background: Whilst the number of students who choose to enrol at institutions of higher education continues to increase, class size remains a challenge. Therefore, institutions of higher education should continuously explore the challenges experienced by students regarding learning in large classes and devise strategies to address such challenges. The experiences of nursing students regarding learning in large classes and its effects on teaching and learning at the University of Namibia (UNAM) and in Namibia are not extensively researched. Objectives: The objective of this study was to explore and describe the experiences of nursing students regarding learning in large classes and its effects on teaching and learning at the UNAM. Methods: A qualitative explorative, descriptive and contextual research design was employed. Data collection was conducted using semi-structured interviews to ascertain the experiences of nursing students regarding learning in large classes and its effects on teaching and learning at the UNAM. Fifteen undergraduate nursing students from the Rundu campus participated in the study using a purposive sampling technique. Results: The analysis of data led to the emergence of the following themes namely: negative learning experiences, positive learning experiences and mechanisms for improvement. The findings had a negative effect on participants' learning outcomes. Conclusion: Findings from this study indicated that participants were dissatisfied with the size of their classes as the learning environment was not conducive for teaching and learning.